Analysis of a sociological survey on information and educational needs of specialists in the field of medicines circulation as regards the issue of medicines interchangeability - N. G. Goloenko; R. I. Yagudina; B. K. Romanov; R. N. Alyautdin; D. G. Karapetyan; E. G. Zelenova; E. E. Arinina; A. Yu. Kulikov; M. V. Protsenko; G. T. Abdrashitova (Регуляторные исследования и экспертиза лекарственных средств)
The article summarises the results of a 2015 survey of healthcare professionals and pharmacists that was aimed to reveal their educational needs on the subject of interchangeable medicines. It was discovered that the respondents were not sufficiently informed about interchangeability of medicines, because independent exploration of regulatory framework does not help to get to know this topic well enough. The survey helped to identify a group of specialists who needed training in «interchangeability of medicines» more than others.